Rer1p, a Retrieval Receptor for Endoplasmic Reticulum Membrane Proteins, Is Dynamically Localized to the Golgi Apparatus by Coatomer - Sato, Ken; Sato, Miyuki; Nakano, Akihiko (The Journal of cell biology, 2001)
Rer1p, a yeast Golgi membrane protein, is required for the retrieval of a set of endoplasmic reticulum (ER) membrane proteins. We present the first evidence that Rer1p directly interacts with the transmembrane domain (TMD) of Sec12p which contains a retrieval signal. A green fluorescent protein (GFP) fusion of Rer1p rapidly cycles between the Golgi and the ER. Either a lesion of coatomer or deletion of the COOH-terminal tail of Rer1p causes its mislocalization to the vacuole. The COOH-terminal Rer1p tail interacts in vitro with a coatomer complex containing α and γ subunits. These findings not only give the proof that Rer1p is a novel type of retrieval receptor recognizing the TMD in the Golgi but also indicate that coatomer actively regulates the function and localization of Rer1p.